Eaters of the dead : the manuscript of Ibn Fadlan, relating his experiences with the Northmen in A.D. 922 - Crichton, Michael, 1942-2008 (New York : Harper, 2009)
It is 922 A.D. The refined Arab courtier Ibn Fadlan is accompanying a party of Viking warriors back to the north. Fadlan belatedly discovers that his job is to combat the terrors in the night that come to slaughter the Vikings-- but just how he will do it, Fadlan has no idea
"Previously published by Ballantine Books under the movie title of, The 13th Warrior"--T.p. verso
Includes bibliographical references (p. [241]-243)
Keywords: d; Beowulf -- Adaptations; Epic poetry, English (Old) -- Adaptations; Middle Ages -- Fiction; Northmen -- Fiction; Vikings -- Fiction; Historical fiction; Fantasy fiction